A Presheaf Semantics of Value-Passing Processes - Winskel, Glynn (BRICS Report Series, 1996)
This paper investigates presheaf models for process calculi with value passing. Denotational semantics in presheaf models are shown to correspond to operational semantics in that bisimulation obtained from open maps is proved to coincide with bisimulation as defined traditionally from the operational semantics. Both "early" and "late" semantics are considered, though the more interesting "late" semantics is emphasised. A presheaf model and denotational semantics is proposed for a language allowing process passing, though there remains the problem of relating the notion of bisimulation obtained from open maps to a more traditional definition from the operational semantics. A tentative beginning is made of a "domain theory" supporting presheaf models.